1997
DOI: 10.1017/s0022215100137326
|View full text |Cite
|
Sign up to set email alerts
|

A homemade modification of a spacer device for delivery of bronchodilator or steroid therapy in patients with tracheostomies

Abstract: Patients who have artificial airways and who concurrently suffer with chronic obstructive airways disease encounter problems when administering inhaled bronchodilator and corticosteroid drugs via the tracheostomy. This is because most of the devices are designed to deliver the metered dose of inhaled drugs via the oropharyngeal route and it is impossible to obtain an airtight seal from the inhaler device mouthpiece to the tracheostomy tube. The author describes a simple, effective and cheap modification of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…2 Pressurized metered-dose inhalers (pMDIs), nebulizers, and dry powder inhalers have been adapted for aerosol delivery through tracheostomy tubes. [3][4][5][6][7][8][9][10][11][12] A few in vitro studies, mostly using adult models, have provided some information regarding the intricacies of delivering aerosol through an artificial airway. [13][14][15][16] These studies showed that aerosol delivery is significantly affected by tracheostomy tube size, interface, type and configuration of add-on devices, use of assisted breathing, and bias flow.…”
Section: Introductionmentioning
confidence: 99%
“…2 Pressurized metered-dose inhalers (pMDIs), nebulizers, and dry powder inhalers have been adapted for aerosol delivery through tracheostomy tubes. [3][4][5][6][7][8][9][10][11][12] A few in vitro studies, mostly using adult models, have provided some information regarding the intricacies of delivering aerosol through an artificial airway. [13][14][15][16] These studies showed that aerosol delivery is significantly affected by tracheostomy tube size, interface, type and configuration of add-on devices, use of assisted breathing, and bias flow.…”
Section: Introductionmentioning
confidence: 99%
“…Different delivery devices including pressurized metered dose inhalers (pMDI), nebulizers and dry powder inhalers have been adapted to deliver inhaled medications through tracheostomies . Few in vitro studies using adult models have provided some insight into the complexity of aerosol delivery through tracheostomies .…”
Section: Introductionmentioning
confidence: 99%
“…Only a few in vitro studies have been done on aerosol delivery through a tracheostomy tube, [106][107][108][109] along with a few case reports on methods used to adapt pMDIs to patients with tracheostomies. [110][111][112] Previous studies found that a measurable amount of aerosol was delivered through the tracheostomy tube regardless of the type of aerosol device used, and aerosol delivery through the tracheostomy tube ranged from 1 to 45% depending on a variety of measurement conditions. [106][107][108][109] Factors affecting pulmonary deposition of aerosols in patients receiving mechanical ventilation are different from those in spontaneously breathing patients.…”
Section: Factors Affecting Aerosol Delivery In Spontaneously Breathinmentioning
confidence: 99%